Alzheimer's disease drug development pipeline: 2020 - Cummings, Jeffrey; Lee, Garam; Ritter, Aaron; Sabbagh, Marwan; Zhong, Kate (Alzheimer's & dementia : translational research & clinical interventions, 2020)
Introduction Alzheimer's disease (AD) is a growing public health concern affecting millions of patients worldwide and costing billions of dollars annually. We review the pipeline of drugs and biologics in clinical trials for the treatment of AD. We use the Common Alzheimer's and Related Dementias Research Ontology (CADRO) to classify treatment targets and mechanisms of action. We review our annual pipeline reports for the past 5 years to provide longitudinal insight into clinical trials and drug development for AD. Methods We reviewed ClinicalTrials.gov as of February 27, 2020, and identified all trials of pharmacologic agents currently being developed for treatment of AD as represented on this widely used U.S. Food and Drug Administration registry. Results There are 121 agents in clinical trials for the treatment of AD. Twenty‐nine agents are in 36 Phase 3 trials, 65 agents are in 73 Phase 2 trials, and 27 agents are in 27 Phase 1 trials. Twelve agents in trials target cognitive enhancement and 12 are intended to treat neuropsychiatric and behavioral symptoms. There are 97 agents in disease modification trials. Compared to the 2019 pipeline, there is an increase in the number of disease‐modifying agents targeting pathways other than amyloid or tau. Discussion The 2020 pipeline has innovations in clinical trials and treatment targets that provide hope for greater success in AD drug development programs. Review of clinical trials over the past 5 years show that there is progressive emphasis on non‐amyloid targets, including candidate treatments for inflammation, synapse and neuronal protection, vascular factors, neurogenesis, and epigenetic interventions. There has been a marked growth in repurposed agents in the pipeline.